P–681 Will the hCG trigger dose used for final oocyte maturation in IVF impact endogenous progesterone during the luteal phase? - A randomized controlled trial. (6th August 2021) - Svenstrup, L; Fedder, J; Möller, S; Pedersen, D; Erb, K; Ydin. Andersen, C; Humaidan, P
Abstract: Study question: Is there an association between the hCG dose used for ovulation trigger and the endogenous progesterone production during the luteal phase? Summary answer: Increased hCG dosing significantly increased the endogenous progesterone level during the luteal phase. What is known already: During the luteal phase of an IVF treatment, the endogenous progesterone (P4) production is negatively impacted due to reduced circulating endogenous LH, caused by negative feed-back of elevated steroids; thus, luteal phase support (LPS) with exogenous P4 remains mandatory in IVF. Apart from inducing final oocyte maturation, the gold standard HCG trigger also functions as an early LPS, boosting P4 production by the corpora lutea (CL). P4 plays a pivotal role for embryo implantation and pregnancy, and an optimal P4 level around peri-implantation seems to be essential for the reproductive outcomes of fresh and frozen/thaw embryo transfer cycles. Study design, size, duration: A randomized controlled 4-arm study, including a total of 127 IVF patients, enrolled from January 2015 until September 2019 at the Fertility Clinic, Odense University Hospital, Denmark. Participants/materials, setting, methods: IVF patients with ≤ 11 follicles ≥ 12 mm were randomized to four groups. Groups 1–3 were triggered with: 5.000 IU, 6.500 IU or 10.000 IU, hCG, respectively, receiving a LPS consisting of 17-α-hydroxy-progesterone (17α OH P4) to distinguish the endogenous P4 from the exogenous supplementation. Group 4 (control) was randomized to a 6.500 IU hCG trigger and standard LPS. A total of eight blood samples were drawn during the early luteal phase. Main results and the role of chance: A total of 94 patients completed the study: 21, 22, 25 and 26 patients in each group, respectively. Baseline characteristics were similar, except for the endogenous LH level and cycle lengths. There were no significant differences between groups regarding ovarian stimulation, number of oocytes and embryos. The median number of follicles ≥ 12mm on the day of trigger was 8.5, resulting in 6.6 oocytes being retrieved. Significant differences in P4 levels were seen at OPU+8 (p < 0.001), OPU+10 (p < 0.001) and OPU+14 (p < 0.001), with positive correlations between P4 level and hCG dose. Groups compared individually showed significant difference in P4 between low and high trigger dose at OPU+4 group 1 and 3 (p = 0.037) and OPU+8 group 1 and 3 (p = 0.007) and between all the three groups around implantation at OPU+6 group 1 and 2 (p = 0.011), group 2 and 3 (p = 0.042) and group 1 and 3 (p < 0.001). Higher P4 levels around implantation were related to follicle count and to pregnancy. After logistic regression analyses there were still significant individual differences between the groups. Limitations, reasons for caution: Although patients were randomized and strict inclusion and exclusion criteria were used, the RCT was un-blinded, including a relatively small number of patients. Moreover, for dosing purposes urinary hCG as well as recombinant hCG was used and pharmacokinetics differ. Finally, the P4 level could be influenced by circadian fluctuations. Wider implications of the findings: This is the first study to explore dose-responses in circulating P4 after hCG trigger in IVF patients. Increasing the hCG trigger dose increased the endogenous P4 around peri-implantation. Personalizing the hCG trigger dose could be a key point to secure the most optimal P4 mid-luteal phase P4 level. Trial registration number: Eudract 2013–003304–39